Impact of high-sensitivity Troponin T on hospital admission, resources utilization, and outcomes. Issue 2 (April 2015) - Corsini, Anna; Vagnarelli, Fabio; Bugani, Giulia; Bacchi Reggiani, Maria Letizia; Semprini, Franco; Nanni, Samuele; Cinti, Laura; Norscini, Giulia; Vannini, Antonio; Beltrandi, Elisabetta; Cavazza, Mario; Branzi, Angelo; et al.
Aims: The use of high-sensitivity cardiac Troponin T (hs-cTnT) assay might lead to overdiagnosis and overtreatment of Acute Coronary Syndromes (ACS). This study assessed the epidemiological, clinical and prognostic impact of introducing hs-cTnT in the everyday clinical practice of an Emergency Department. Methods and Results: We compared all consecutive patients presenting with suspected ACS at the Emergency Department, for whom troponin levels were measured. In particular, we considered 597 patients presenting during March 2010, when standard cardiac Troponin T (cTnT) assay was used, and 629 patients presenting during March 2011, when hs-cTnT test was used. Patients with suspected ACS and troponin levels above the 99th percentile (Upper Reference Limit, URL) significantly increased when using an hs-cTnT assay (17.2% vs. 37.4%, p < 0.001). Accordingly, also the mean GRACE risk score increased (124.2 ± 37.2 vs. 136.7 ± 32.2; p < 0.001). However, the final diagnosis of Acute Myocardial Infarction (AMI) did not change significantly (8.7% vs. 6.8%, p =0.263) by using a rising and/or falling pattern of hs-cTnT (change ≥ 50% or ≥ 20% depending on baseline values). In addition, no significant differences were found between the two study groups with respect to in-hospital (2.7% vs. 1.9%, p =0.366) and 1-year mortality (9.8% vs. 7.6%, p =0.216). Conclusions: We did not observe overdiagnosis and overtreatment issues in presenters with suspected ACS managed by appropriate changes in hs-cTnT levels, despite the increase in the number of patients presenting with abnormal troponin levels. This occurred without a rise in short-term and mid-term mortality.